Harmonisasi Kebijakan Pengendalian Daya Rusak Air dalam Kerangka Tata Kelola Berkelanjutan di Indonesia - Pambudi, Andi Setyo; Bambang Pramujo (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Indonesia faces a significant increase in water-related hazards such as floods, droughts, erosion, and landslides, all of which have broad socio-economic and environmental impacts. This research originates from a gap between a relatively strong legal framework for water damage control (PDRA) and its fragmented implementation across sectors such as water resources, environment, disaster management, and spatial planning. Weak inter-agency coordination and regulatory disharmony have led to budget inefficiencies and low effectiveness in water damage mitigation. The urgency of this study lies in the need to establish a harmonized policy model aligned with the policy coherence for sustainable development framework as mandated in the 2025–2045 National Long-Term Development Plan (RPJPN). This study adopts a mixed-methods approach combining regulatory content analysis, in-depth interviews, and inter-agency focus group discussions (FGDs). The main findings reveal overlapping policies, weak cross-sectoral coordination, and inconsistencies among spatial, watershed, and disaster management planning. As a solution, this research proposes the “Four Pillars of PDRA Harmonization” model, which includes regulatory synchronization, collaborative institutions, sustainable financing, and integrated national data systems. The study recommends the establishment of a unified national water governance framework, the creation of a cross-sectoral coordination committee, and the adoption of performance-based budgeting to strengthen sustainable water governance toward a resilient and prosperous Indonesia 2045.